Adipose Tissue and Serum CCDC80 in Obesity and Its Association with Related Metabolic Disease - Óscar Osorio-Conles; María Guitart; José María Moreno-Navarrete; Xavier Escoté; Xavier Duran; José Manuel Fernandez-Real; Anna María Gómez-Foix; Sonia Fernández-Veledo; Joan Vendrell (BMC, 2017)
Abstract Coiled-coil domain-containing 80 (CCDC80) is an adipocyte-secreted protein that modulates glucose homeostasis in response to diet-induced obesity in mice. The objective of this study was to analyze the link between human CCDC80 and obesity. CCDC80 protein expression was assessed in paired visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) from 10 patients (body mass index range 22.4-38.8 kg/m2). Circulating CCDC80 levels were quantified in serum samples from two independent cross-sectional cohorts comprising 33 lean and 15 obese (cohort 1) and 32 morbidly obese (cohort 2) male patients. Insulin sensitivity, insulin secretion and blood neutrophil count were quantified in serum samples from both cohorts. Additionally, circulating free insulin-like growth factor (IGF)-1 levels and oral glucose tolerance tests were assessed in cohort 1, whereas C-reactive protein levels and degree of atherosclerosis and hepatic steatosis were studied in cohort 2. In lean patients, total CCDC80 protein content assessed by immunoblotting was lower in VAT than in SAT. In obese patients, CCDC80 was increased in VAT (P < 0.05) but equivalent in SAT compared with lean counterparts. In cohort 1, serum CCDC80 correlated negatively with the acute insulin response to glucose and IGF-1 levels and positively with blood neutrophil count independent of BMI, but not with insulin sensitivity. In cohort 2, serum CCDC80 was positively linked to the inflammatory biomarker C-reactive protein (r = 0.46; P = 0.009), atherosclerosis (carotid intima-media thickness, r = 0.62; P < 0.001) and hepatic steatosis (analysis of variance P = 0.025). Overall, these results suggest for the first time that CCDC80 may be a component of the obesity-altered secretome in VAT and could act as an adipokine whose circulant levels are linked to glucose tolerance derangements and related to inflammation-associated chronic complications.